The Effect of Implementing the Balanced Scorecard on the Management Performance of PT YKK AP Indonesia - Irwanto, Endrik; Nopriana, Wiwin; Nisah, Ainun; Ratnandari, Anditya Anggun (International Journal of Finance Research, 2024)
This study aims to determine the effect of a balanced scorecard on the management performance of PT. YKK AP Indonesia. This study used 40 employees of PT. YKK AP Indonesia, who met the criteria to be respondents. This study was conducted using the conventional sampling method on PT employees. YKK AP Indonesia and analyzed using multiple linear regression. The first stage tested the validity and reliability of questions for each variable. The second stage conducted a classical test, and the third stage conducted an F test, t-test, and determination coefficient test. The results of the t-test study showed that the variables of financial perspective, customer perspective, internal business process perspective, and growth and learning perspective had a partial effect on management performance. In the F test, all independent variables simultaneously affected the dependent variable. Meanwhile, the determination coefficient value shows that the independent variables of financial perspective, customer perspective, internal business process perspective, and growth and learning perspective contributed to the dependent variable, namely management performance, by 49%, while other factors outside the model influenced the remaining 51%.